Ilmu Kepolisian dalam Perspektif European Police College - Eko Rudi Sudarto (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2026)
Police science has evolved alongside the increasing complexity of policing functions in modern society. In Europe, its development gained significant momentum through the initiatives of the European Police College (CEPOL), which promotes an integrated scientific approach to policing. This article aims to analyze the concept of police science from the CEPOL perspective based on the report Perspectives of Police Science in Europe. The study employs a qualitative library research method through the analysis of official CEPOL documents. The findings indicate that to enhance police professionalism, police science is understood as an interdisciplinary applied discipline integrating law, criminology, sociology, psychology, and management. CEPOL emphasizes the interconnection between research, education, and operational practice, as well as the importance of democracy, human rights, and the rule of law as the fundamental principles guiding policing in addressing contemporary security challenges. In the context of current global issues, such as transnational crime, terrorism, irregular migration, cybercrime, and hybrid threats, a knowledge-based police science approach has become increasingly relevant for strengthening the adaptive capacity of police institutions. For Indonesia, the CEPOL perspective provides a valuable conceptual framework for the development of police science capable of responding to evolving national security challenges, including the management of transnational crime, digital transformation in policing, and the strengthening of democratic and accountable security governance.